A Survey of Education Program Needs for the Florida Association of Counties County Commissioner Training Program, 1998-2000 - Rodney L. Clouser (EDIS)
FE640, a 27-page fact sheet by Rodney L. Clouser, includes an Executive summary of results of the 1998-2000 survey (2 p.), the survey itself (3 p.) and 21 plates of graphs depicting the responses to the survey questions. Published by the UF Food and Resource Economics Department, June 2006.